'What harbour shelters peace?' On the opera Peter Grimes, exclusion and stigma. Issue 3 (2nd May 2014) - Conlan, Lisa
Summary: Benjamin Britten's opera Peter Grimes premiered in 1945 and has since enjoyed lasting popular and critical acclaim. Its central character is a fisherman driven to suicide by circumstances beyond his control. It has a wide political and social resonance and is a testament to the damaging psychological effects of exclusion and stigma.